Agrarian studies : synthetic work at the cutting edge - Scott, James C.; Bhatt, Nina (Yale agrarian studies., 2001)
This book presents an account of an intellectual breakthrough in the study of rural society and agriculture. Its ten chapters, selected for their originality and synthesis from the colloquia of the Programme in Agrarian Studies at Yale University, encompass various disciplines, diverse historical periods, and several regions of the world. The contributors' fresh analyses will broaden the perspectives of readers with interests as wide-ranging as rural sociology, environmentalism, political science, history, anthropology, economics, and art history. The ten studies recast and expand what is known about rural society and agrarian issues, examining such topics as poverty, subsistence, cultivation, ecology, justice, art, custom, law, ritual life, cooperation, and state action. Each contribution provides a point of departure for new study, encouraging deeper thinking across disciplinary boundaries and frontiers.